2 - Théories de la régulation et développement: la formation du sous-développement au Burundi: by Hakim Ben Hammouda - Hakim Ben Hammouda (Africa Development, 1994)
The stability and coherence of the accumulation process requires a perfect control of the social norms of reproduction such as the monetary norm, the price norm and the technical norm A detailed analysis of these parameters for the evolution of the history of Burundi from pre to postcolonial period shows that all that the Belgium colonial power did was rather destructive. Indeed, the major objectives of these parameters which were to stabilise and autonomise the accu- mulation process have been perverted and instead of a balance between the social needs and production, what happened was a deeper integration of Burundi in the area of domination controlled by Belgium and a reorientation of the dynamics of ac- cumulation towards the reproduction and stability of the system.